THE DEVELOPMENT OF LEARNING MANAGEMENT ABILITY OF BASIC EDUCATION SCHOOLS TEACHERS IN NAKHON RATCHASIMA TO IMPROVE 21st CENTURY STUDENTS’ LEARNING RESULTS BY USING COOPERATIVE LEARNING - ธงภักดี, ลลิตา; จุลศิริพงษ์, สิทธิศักดิ์ (Research Community and Social Development Journal, 2018)
The purpose of this research was to: 1) develop the teachers’ collaborative learning management skills, 2) study the students’ learning achievement with their collaboration skills, and 3) revise the teachers’ satisfaction on the research project. By using purposive sampling method upon their consent, the target group assigned in the study consisted of 10 teachers, in Nakhon Ratchasima Basic Education Schools. The research instruments used in this study were the teacher's learning log, lesson plan evaluation form, learning achievement test, cooperative learning skills checklist, students’ satisfactory evaluation form, teachers’ learning and teaching ability evaluation form and reflection form towards teachers’ lesson summary. Descriptive statistics were content and analysis. The results were 1) teachers’ ability towards instructional design and teachers’ ability towards cooperative learning management in general was reported at high level, 2) students’ learning outcomes were from cooperative learning management which showed the higher achievement scores of students after the study, the collaborative skills scores also increase after class, and 3) overall teachers’ satisfaction towards the research project was at the highest level.